Analisis Komparatif dan Model Integrasi Reliability-Centered Maintenance (RCM) dan Total Productive Maintenance (TPM) dalam Industri Manufaktur - Bambang Triono; Didit Darmawan (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
This systematic literature study conducts a comparative analysis of Reliability-Centered Maintenance (RCM) and Total Productive Maintenance (TPM) in manufacturing, and proposes an integrated hybrid model. The research concludes that RCM and TPM are fundamentally distinct methodologies: RCM excels in risk-based, analytical management of complex, high-criticality assets, while TPM is superior for achieving broad-based productivity gains and cultural empowerment through total employee involvement. The effectiveness of each approach is contingent upon factors such as asset characteristics, organizational culture, data availability, and level of automation. To leverage their complementary strengths, the study proposes the Synergistic RCM-TPM Hybrid Model (SRTHM). This framework advocates for a sequential implementation where TPM establishes the foundational operational stability, discipline, and data culture, upon which selective RCM analysis is applied to critical assets for precision risk management. The model incorporates explicit feedback mechanisms to create a continuous organizational learning cycle. The study provides a contingency framework for methodology selection and a practical roadmap for integration, offering theoretical and practical guidance for building more resilient and context-appropriate maintenance systems in modern manufacturing.